2009
DOI: 10.1002/etc.3
|View full text |Cite
|
Sign up to set email alerts
|

Reconcilable differences: The use of reference material to reduce methodological artifacts in the reporting of organochlorine pesticides and polychlorinated biphenyls

Abstract: Numerous long-term monitoring programs have assessed spatial and temporal trends of organochlorine (OC) pesticides and polychlorinated biphenyls (PCBs). Changes in analytical approaches (e.g., gas chromatography coupled with electron capture detection [GC-ECD] versus mass spectrometric detection [GC-MSD]) can reveal artifacts in the reported concentrations. In-house reference material (RM) was used to determine the analytical artifacts in the measurement of OCs and PCBs in Great Lake herring gull eggs previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Although we support the use of conversion factors [8,27], they should be used cautiously, because incorrect conversions could make the situation worse. Some previous attempts at creating conversion factors revealed that the conversion factors may vary with matrix; relationships between Aroclor-based and congener-specific methods of quantification differed among water, sediment and aquatic animals, and even species [31].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Although we support the use of conversion factors [8,27], they should be used cautiously, because incorrect conversions could make the situation worse. Some previous attempts at creating conversion factors revealed that the conversion factors may vary with matrix; relationships between Aroclor-based and congener-specific methods of quantification differed among water, sediment and aquatic animals, and even species [31].…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, dioxins and non-ortho PCB concentrations in food for human consumption measured at different laboratories were not numerically comparable [7]. Our earlier study demonstrated differences in quantification of OC compounds between detectors [8] and also differences in technique (see Materials and Methods), and extraction and cleanup also may contribute to discrepancies in the measured concentrations.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations